Parkinson Disease: An Evolutionary Perspective - Garcia-Ruiz, Pedro J.; Espay, Alberto J. (Frontiers in Neurology, 2017)
There are two central premises to this evolutionary view of Parkinson disease (PD). First, PD is a specific human disease. Second, the prevalence of PD has increased over the course of human history. Several lines of evidence may explain why PD appears to be restricted to the human species. The major manifestations of PD are the consequence of degeneration in the dopamine-synthesizing neurons of the mesostriatal neuronal pathway. It is of note the enormous expansion of the human dopamine mesencephalic neurons onto the striatum compared with other mammals. Hence, an evolutionary bottle neck was reached with the expansion of the massive nigrostriatal axonal arborization. This peculiar nigral overload may partly explain the selective fragility of the human dopaminergic mesencephalic neurotransmission and the unique presence of PD in humans On the other hand, several facts may explain the increasing prevalence of PD over the centuries. The apparently low prevalence of PD before the 20th century may be related to the shorter life expectancy and survival compared to present times. In addition, changes in lifestyle over the course of human history might also account for the increasing burden of PD. Our hunter-gatherers ancestors invested large energy expenditure on a daily basis, a prototypical physical way of life for which our genome remains adapted. Technological advances have led to a dramatic reduction of physical exercise. Since the brain release of neurotrophic factors (including BDNF) is partially exercise-related, the marked reduction in exercise may contribute to the increasing prevalence of PD